Dielectric Properties of BaZr0.2[Ti(1-x)Mgx/3Ta2x/3]0.8O3 Solid Solution - Kavil, Jithesh; Varghese, Jobin; Kovummal, Govind Raj (Frontiers in Materials, 2021)
BaZr0.2[Ti(1-x)Mgx/3Ta2x/3]0.8O3 (x=0.0, 0.05, 0.1, 0.2, 0.4, 0.6, 0.8, 1.0) (BZTMT) ceramics were prepared through conventional solid-state ceramic route. The crystal structure and microstructure of the compounds were investigated respectively using XRD and SEM. The dielectric properties were measured in the frequency range of 100 Hz -1 MHz. The ferroelectric Curie temperature of BaZr0.2Ti0.8O3 (x=0) shifted from 21 °C to -10 °C with the addition of a minute amount of dopant (x=0.025) and the paraelectric transition temperature is diffusive in nature. The relative permittivity and dielectric loss of BZTMT vary from 5205 to 24 and 1.8x10-2 to 2.0x10-5 respectively, as the value of x increases from 0 to 1.